Remember the past, plan for the future: How interactions between risk perception and behavior during the COVID-19 pandemic can inform future Canadian public health policy - Law, Moira A.; Wilbiks, Jonathan M. P.; Roach, Sean P.; Best, Lisa A. (Frontiers in Public Health, 2022)
The ongoing COVID-19 pandemic necessitated the implementation of numerous temporary public health policies, including social distancing, masking, and movement limitations. These types of measures require most citizens to follow them to be effective at a population level. This study examined population adherence to emergency public health measures using early data collected in the Spring of 2020, when all Canadian jurisdictions were under relatively strict measures. In total, 1369 participants completed an online questionnaire package to assess adherence, perceptions of government response, and perceptions of COVID-19 risk. Results indicated that most Canadians were pleased with the government’s handling of the early phases of the pandemic and immediately engaged new public health mandates. Willingness to change behaviours was unrelated to satisfaction with the government response. Similarly, behavioural adherence was also unrelated to satisfaction with government, or personal risk perceptions; however, adherence to public health guidelines was related to elevated psychological distress. As the pandemic continues, public health officials must balance the mental health of the population with the physical health concerns posed by COVID-19 when applying public health mandates.